Bioinformatics Analysis, Prokaryotic Expression and Biological Activity of Lysin from Vibrio parahaemolyticus Phage vB_VpP_1 - ZHANG Defu, YANG Wenjing, LIU Ke, LIU Qingqing, BAI Wutong, LI Fan, LÜ Xinran, BAI Xue, TAN Xiqian, LI Xuepeng, LI Jianrong (Shipin Kexue, 2025)
To study the in vitro cleavage effect of a recombinant lysin from bacteriophage vB_VpP_1 on Vibrio parahaemolyticus, the gp32 gene fragment of vB_VpP_1 was identified as a lysin gene according to the results of whole-genome sequencing (WGS) and functional analysis. The amino acid sequence and structure of gp32 were analyzed by various tools such as Expasy. Primers were designed using Primer 5.0 software and cloned into the pET-28a(+) vector for prokaryotic expression. The lytic activity of the purified lysin against the host bacterium before and after being treated with ethylene diamine tetraacetic acid (EDTA) was measured. Tertiary structure analysis showed that the lysin was a spherical hydrophilic protein, which was predicted to contain two catalytic domains. This was consistent with the basic characteristics of Gram-negative phage lysins. The lysin had no transmembrane region or signal peptide. The purified bacteriophage vB_VpP_1 had a lysin activity of approximately (1 487 ± 182) U/mg, which showed a strong capacity to lyse V. parahaemolyticus with damaged cell walls but not V. parahaemolyticus with intact cell walls. The prokaryotic expression vector for bacteriophage vB_VpP_1 lysin was successfully constructed, and the expressed and purified lysin could lyse V. parahaemolyticus with damaged cell walls.